Philemon: imagination, labor, and love - Seesengood, Robert Paul (T&T Clark study guides to the New Testament, 2020)
Introduction : On reading lost letters -- A quick overview of Paul's letter to Philemon -- I appeal to you for my child, Onesimus -- Rethinking Onesimus and Philemon -- Labor and love: an affect reading of Philemon -- Conclusion : Letters lost in the mail.